Integrating Bondowoso Kentrung Art into Inquiry-Based Science Learning: Effects on Critical Thinking and Collaboration Skills - Silvia Qaulina Damayanti; Supeno Supeno; Iis Nur Asyiah (Universitas Pendidikan Mandalika, 2026)
Critical thinking and collaboration are 21st-century skills that remain a challenge in science learning. The purpose of this study was to examine the effect of integrating Kentrung Bondowoso art into inquiry-based science learning on critical thinking and collaboration. The research design used was a quasi-experimental study using a pre-test and post-test control group. In the experimental group, inquiry-based science learning was implemented that integrated scientific phenomena found in the Kentrung Bondowoso art, while in the control group, inquiry-based science teaching was conducted. Critical thinking was assessed through an essay test, and collaboration was evaluated using an observation sheet. Descriptive statistical analysis was conducted to determine the mean, standard deviation, and level of achievement gain. The ANCOVA test was applied to determine the impact of learning innovation on critical thinking and collaboration. The results of statistical tests showed that between the experimental group and the control group, there was a significant difference in critical thinking (p < .05), and there was no significant difference in collaboration (p > .05). The findings showed that integrating Kentrung Bondowoso art into inquiry-based science learning significantly influenced critical thinking but did not significantly affect collaboration. Students use the local cultural context to develop their thinking processes. This research result implies that the use of local cultural contexts, such as the Kentrung Bondowoso art form, continues to hold significant pedagogical value in science teaching, particularly in enhancing the relevance and meaningfulness of learning.